The gene for a novel human lamin maps at a highly transcribed locus of chromosome 19 which replicates at the onset of S-phase. - Biamonti, G (1992)
A previously described human DNA fragment which is replicated early in S-phase of HL-60 cell DNA (C. Tribioli, G. Biamonti, M. Giacca, M. Colonna, S. Riva, and A. Falaschi, Nucleic Acids Res. 15:10211-10232, 1987) was used to screen a genomic library in lambda Ch28. A clone which contained a 13.7-kb insert (L30E) found to code for several transcripts was isolated. The transcription of L30E DNA exhibited a complex pattern and a tissue-specific and proliferation-dependent type of regulation. The data were consistent with two tandemly arranged transcription units, the 3' end of one separated from the 5' end of the other by a sequence of about 600 bp containing an active promoter. The isolation and sequencing of L30E-specific cDNAs permitted identification of two genes, one of which encoded a B-type human lamin (analogous to mouse lamin B2). L30E DNA was mapped by in situ hybridization at the G-negative subtelomeric band p13.3 of chromosome 19. Interestingly, in synchronized HL-60 cells, L30E DNA is replicated in the first minute of S-phase. Replication of the lamin gene early in S-phase may reflect a coupling between early replication and transcription of genes for S-phase-specific proteins such as lamins.